Evaluation of Antidiabetic Activity of Corchorus trilocularis Linn Plant Extract: Pharmaceutical Science-Pharmacology - Omer, Shaista; Vidyadhara, Suryadevara; Sandeep, Doppalapudi (International Journal of Life Science and Pharma Research, 2022)
Diabetes is a major health issue that has been faced by the majority of the population in the world. Extensive research is being carried out towards development of an antidiabetic component. The aim of the present research was to determine the antidiabetic activity of Corchorus trilocularis Linn plant belonging to the Tiliaceae family. The objectives were to evaluate various serum and pancreatic parameters related to evaluation of diabetes. The whole plant was extracted using various solvents. Phytochemical screening was done for the extracts. Antidiabetic activity was determined using Streptozotocin (STZ) induced diabetes model in rats using 200 mg/kg and 400 mg/kg doses of various extracts. Biochemical components like glycosylated hemoglobin (HbA1c), glutathione, creatine kinase (CK) and lactate dehydrogenase (LDH) were estimated for the collected blood samples from rats. The pancreatic tissue was homogenized and the result was subjected for estimation of TBARS (thiobarbituric acid-reactive substances), catalase, superoxide dismutase (SOD) and glutathione (GSH). Phytochemical screening showed presence of carbohydrates, glycosides, alkaloids, triterpenes, phytosterols, tannins, flavonoids, saponins, mucilage and steroids. The chloroform extract at 400 mg/kg dose significantly lowered the levels of HbA1c and restored blood GSH levels. The levels of CK and LDH were increased in diabetic rats. The treatment with chloroform extract (400 mg/kg) for 21 days significantly reduced the levels of CK when compared to diabetic rats. Extent of TBARS formed was significantly higher (p<0.001) in STZ treated group. In chloroform extract (400 mg/kg) treated groups, TBARS levels have significantly decreased (p<0.001). Diabetic rats treated with chloroform extract (400 mg/kg) showed significant increase (p<0.01) in levels of SOD. GSH activity was reduced in pancreatic tissue of diabetic rats, compared to normal animals. These levels were significantly (p<0.01, p<0.001) increased with chloroform extracts (200 mg/kg and 400 mg/kg) treatment. Thus the present study showed the antidiabetic potency of Corchorus trilocularis Linn plant.